Mapping global trends in green consumption (2014–2024): A bibliometric analysis of emerging insights and directions - Qin Lingda Tan; Sharizal Bin Hashim; Zhangwei Zheng (Sustainable Futures)
This study analyzes 1592 Scopus-indexed publications from 2014 to 2024 to map research trends in green consumption. The analysis identifies a citation surge in 2016, marking key contributions that shaped the discourse. A global collaboration network has emerged, with China as a leading hub and significant contributions from scholars in Malaysia, India, and other countries. Key journals, such as Sustainability and the Journal of Cleaner Production, have played pivotal roles in disseminating influential research. Four thematic research clusters were identified: psychological drivers, macro-environmental impacts, market dynamics and technological innovations, and policy frameworks. Core keywords, such as ''environmental values'' and ''green purchase intention,'' highlight a focus on eco-friendly purchasing behaviors, while emerging terms, such as ''green technology'' and ''digital platforms,'' reflect the growing role of technological solutions in sustainable consumption. The study underscores a shift toward interdisciplinary research, integrating consumer psychology, marketing strategies, and digital innovations to address sustainability challenges. It provides a comprehensive overview of the green consumption research landscape and outlines future research priorities to advance sustainable consumption practices globally.